RELATIONSHIPS BETWEEN EXAM PERFORMANCE AND SOME BIOCHEMICAL PARAMETERS - JWAN ABDULMOHSIN ZAINULABDEEN; MOHAMMED MAHDI SAMI (International Journal of Pharma and Bio Sciences, 2016)
Examination stress is an ordinary and prevalent phenomenon for students, so the aim of this study was to investigate the relation of exam performance and first semester score with some biochemical parameters in sera of undergraduate students affecting by temporarily examination stress. Fifty five apparently healthy undergraduate students were enrolled in this study, their age was ranging from 19 to 24 years and the mean values of BMI were (24.20 ± 2.6 kg/m2). A blood sample was collected in two times from each student, firstly was on the morning of a written exam (Exam day or E-day) and secondly was in the day that the students do not have any exam (Normal day or N-day). The serum cortisol, fasting blood glucose, amylase activity, and albumin were measured by spectrophotometry, while total serum copper, iron, and zinc ions were measured by flame atomic absorption technique. The results (comparing E-day with N-day) were indicated that the examination stress is related to the exam performance and first semester score; meanwhile there were relations between fasting blood glucose and copper levels with exam performance and also with first semester score.